2022
DOI: 10.1021/acs.est.1c07950
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Personal Exposure to Particulate Nitrated Phenols from Heating Energy Renovation in China: The First Assessment on Associated Toxicological Impacts with Particle Size Distributions

Abstract: The clean heating renovation has been executed for improving particulate matter (PM) pollution in northern China since 2017. This study determined particle size distributions of nitrated phenols (NPs) in personal exposure samples and their associations with biomarkers in saliva and urine from homemakers in rural households of the Fenwei Plain, China. Remarkable reductions of 28.6–66.3% and 52.2–82.4% on PMs and total quantified NPs, respectively, were found with the substitutions of raw coal chunk and biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Previous studies have assessed the effects of certain NACs, such as the vasodilatory, estrogenic, and antiandrogenic activities of 4-NP, 2-methyl-4NP, and 3-methyl-4NP by rat thoracic artery and in vitro assays . Eleven NACs in PM 2.5 showed positive correlations with interleukin (IL)-6 and 8-hydrox-2′-deoxyguanosine (8-OHdG) in urine and saliva of 18 homemakers . However, a comprehensive investigation of NACs based on exposure markers is largely absent from the literatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have assessed the effects of certain NACs, such as the vasodilatory, estrogenic, and antiandrogenic activities of 4-NP, 2-methyl-4NP, and 3-methyl-4NP by rat thoracic artery and in vitro assays . Eleven NACs in PM 2.5 showed positive correlations with interleukin (IL)-6 and 8-hydrox-2′-deoxyguanosine (8-OHdG) in urine and saliva of 18 homemakers . However, a comprehensive investigation of NACs based on exposure markers is largely absent from the literatures.…”
Section: Resultsmentioning
confidence: 99%
“…30 Eleven NACs in PM 2.5 showed positive correlations with interleukin (IL)-6 and 8- hydrox-2′-deoxyguanosine (8-OHdG) in urine and saliva of 18 homemakers. 31 However, a comprehensive investigation of NACs based on exposure markers is largely absent from the literatures.…”
Section: Study Design and Sample Collectionmentioning
confidence: 99%
“…Further, in the north, the DTTv was closely related to the concentrations of NACs (r of 0.57 to 0.79) (Figure S2), suggesting that NACs could be important contributors to DTT consumption. Feng et al (2022) reported the positive correlations between NACs and biomarkers in saliva and urine (interleukin-6 and 8-hydrox-2ʹ-deoxyguanosine). Zhang et al (2023) also reported that NACs are major proinflammatory components in organic aerosols, contributing about 24% of the interleukin-8 response of all compounds detected by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) in electrospray ionization negative mode (ESI-).…”
Section: Correlation Between Dtt Activity and Water-soluble Pm25 Comp...mentioning
confidence: 98%